2015
DOI: 10.1111/gcb.12890
|View full text |Cite
|
Sign up to set email alerts
|

The timing of autumn senescence is affected by the timing of spring phenology: implications for predictive models

Abstract: Autumn senescence regulates multiple aspects of ecosystem function, along with associated feedbacks to the climate system. Despite its importance, current understanding of the drivers of senescence is limited, leading to a large spread in predictions of how the timing of senescence, and thus the length of the growing season, will change under future climate conditions. The most commonly held paradigm is that temperature and photoperiod are the primary controls, which suggests a future extension of the autumnal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
266
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(295 citation statements)
references
References 66 publications
27
266
2
Order By: Relevance
“…Tropical regions and other land areas (e.g., the boreal region in some studies) were recognized as important players in the changing global terrestrial net primary production and carbon balance [5,6]. Changes in onset and cessation of the growing season are interacting with the carbon cycle [3,7,8], thus accurate estimation of plant phenology is essential [9][10][11][12][13]. All of these studies clearly demonstrate the…”
Section: Introductionmentioning
confidence: 90%
“…Tropical regions and other land areas (e.g., the boreal region in some studies) were recognized as important players in the changing global terrestrial net primary production and carbon balance [5,6]. Changes in onset and cessation of the growing season are interacting with the carbon cycle [3,7,8], thus accurate estimation of plant phenology is essential [9][10][11][12][13]. All of these studies clearly demonstrate the…”
Section: Introductionmentioning
confidence: 90%
“…However, previous authors found that an earlier leaf flushing resulted in an earlier senescence in two tree species of pedunculate oak (Quercus robur L.) and European beech (Fagus sylvatica L.) in Belgium [22]. The timing of autumn senescence was related to the timing of spring bud-burst by using two decades of ground and satellite-based observations of temperate deciduous forest phenology in the northeastern US [23]. A positive correlation between the SOS and EOS was detected from a satellite-observed normalized difference vegetation index over 1982-2011 in the southwestern TP [42].…”
Section: Relationships Between Start and Ending Of The Growing Seasonmentioning
confidence: 99%
“…However, scarce effort has been directed at modeling the induction of dormancy, which is tightly linked to leaf senescence and cold acclimation and, further, impacts spring phenophases. Another example is the partial dependence of leaf senescence on the timing of budburst (Fu et al 2014), which has not been implemented in models to date (but see Keenan and Richardson 2015). This situation indicates the need for a common framework that is representative of the cyclic nature of phenological events (Figs.…”
Section: How Can We Improve Phenological Models?mentioning
confidence: 99%